MANAGEMENT OF GUIDANCE COUNSELING IN ELEMENTARY SCHOOLS - Fauziah, Hana; Kamilah, Maya Sifa Wafa; Badrudin, Badrudin; Yafrizal, Mochamad Varhana (Universitas Nurul Jadid, 2022)
The purpose of this study was to reveal the management of the UPI SD Lab BK. This study uses a qualitative approach. This type of research is a case study. Data collection uses observation techniques, interviews and document studies. The research instrument is a group instrument. The analysis used in this study is an interactive analysis model of Miles and Huberman through data collection, data reduction, data presentation and drawing conclusions. The results of UPI's BK SD Lab management research consisted of planning, organizing, implementing and supervising. Where the planning of the UPI SD Lab BK is flexible, factual and contextual because in preparing the program it never departs from the vision, mission, guidance and goals of the school. The organization involved the principal, wk. Student affairs, subject teachers and homeroom teachers. As for the assignment of guidance, the BK choir divided 5 BK teacher personnel for six generations by combining class 1 coaches with class 4 coaches to be responsible for class 4. The implementation of the BK program itself has been running from daily to annual counseling. And finally, there is an evaluation where the evaluation of SD Upi's guidance is carried out every month and every year, to see the development of students and the development of the guidance counselor himself.